An examination of selected works for percussion; Concerto for marimba and wind ensemble by David Gillingham, XL plus one by Alvin Etler, March from eight pieces for four timpani by Elliott Carter, 42nd street rondo by Wayne Siegel, Oceanus by Steve Houghton and Wendell Yuponce - Whitman, David Robert (Kansas State University, 2008)
This is a report intended for musicians planning to perform any number of, or scholars seeking to enrich understanding of, the following compositions: Concerto for Marimba and Wind Ensemble by David Gillingham, XL Plus One by Alvin Etler, March from Eight Pieces for Four Timpani by Elliott Carter, 42nd Street Rondo by Wayne Siegel, and Oceanus by Steve Houghton and Wendell Yuponce. Each work is analyzed in accordance with Jan Larue's method of style analysis. For some compositions, analysis of harmony has been omitted. For all compositions, the author has added a pedagogical realm of analysis, dedicated to notable performance considerations, interpretive possibilities, and technical considerations, to Larue's organizational scheme. Therefore, the approach taken in this document can be expressed as: Sound, Harmony, Melody, Rhythm, Growth, and Performance.
Keywords: David Gillingham; Alvin Etler; Steve Houghton; Wendell Yuponce; Wayne Siegel; Elliott Carter; Biography (0304); Education, Music (0522); Music (0413)